TINJAUAN TERHADAP LARANGAN MINUMAN BERALKOHOL BERDASARKAN PERATURAN DAERAH NOMOR 6 TAHUN 2013 TENTANG LARANGAN, PENGAWASAN, PENERTIBAN DAN PENJUALAN MINUMAN BERALKOHOL DALAM WILAYAH KOTA SAMARINDA - Nanang Dwi Adianse (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTThe problems related to alcoholic beverages in Indonesia, especially in Samarinda city, are getting more and more alarming. Judging from every control carried out by the authorities, there are not a few stalls and shops without permission to deliberately sell and distribute alcoholic beverages. seller with or without guilt and fear, desperate to sell alcoholic drinks without permission whose adverse effects endanger consumers. Distribution licenses or places to sell alcoholic drinks have been regulated in the Regional Regulation of Samarinda City Number 6 of 2013 concerning Prohibition, Supervision, Control and Sales of Alcoholic Beverages in the Samarinda City area. The Government of Samarinda City as the party granting permits for the sale of alcoholic beverages must play an active role and synergize with the City Police of Samarinda City in supervising the place of sale of illegal alcoholic beverages that carry out their activities. The purpose of this study was to review the normative juridically regarding the prohibition of circulation of alcoholic beverages based on the Regional Regulation of Samarinda City Number 6 of 2013. The factors that caused the circulation of alcoholic beverages in Kota Samarinda were the socio-cultural factors of the city of Samarinda as well, the law enforcement officers' lack of routine in controlling the circulation of alcoholic beverages, alcoholic beverages became one of the livelihoods of the community, regional policy factors, and lack of public awareness in preventing the circulation of alcoholic beverages in their environment. The Resort Police Officers of Samarinda City have made efforts in overcoming the circulation of alcoholic beverages by means of preemptive efforts, preventive efforts, and repressive efforts. Keywords: Review of Regional Regulations, Prohibition of Alcoholic Beverages.